Accelerating an Olympic decathlete`s return to competition using high-frequency blood flow restriction training: a case report - Gaviglio, C.; Bird, S. P. (Sports, 2025)
This case report describes the acceleration of an Olympic decathlete`s return to competition induced via high-frequency Blood Flow Restriction (BFR) training. BFR has gained popularity as an innovative rehabilitation method for promoting muscle repair and adaptation through anabolic and regenerative pathways when high mechanical loading is not possible. A 26-year-old elite decathlete with nine years of international experience sustained a Grade 2b strain of the semimembranosus and semitendinosus (a 9 mm central tendon tear) during a hurdle sprint. The injury was confirmed via MRI two days post-injury. Grade 2b hamstring injuries with intramuscular tendon involvement commonly require up to 4 weeks of rehabilitation before full training can be resumed. With the athlete due to complete in an Olympic Games competition 17 days post-injury, an intensive BFR-assisted rehabilitation program was initiated. Over 12 consecutive days, the athlete completed 3-6 BFR sessions per day (20-30 min each) at 50% limb occlusion pressure, along with physiotherapy and pain-limited functional testing. BFR was applied passively for recovery, during conditioning, and in low-load strength sessions. By day 12, sprint velocity reached 95% maximum, and the athlete successfully completed the decathlon, with no adverse effects or reinjury. This case illustrates how high-frequency BFR-assisted rehabilitation may facilitate accelerated recovery from a hamstring injury, enabling an effective return to elite competition within condensed timelines.